Deterministic Nucleation for Halide Perovskite Thin Films with Large and Uniform Grains. (28th August 2017) - Geske, Thomas; Li, Junqiang; Worden, Matthew; Shan, Xin; Chen, Mingming; Bade, Sri Ganesh R.; Yu, Zhibin
Abstract: Halide perovskite materials have come to the forefront of optoelectronics recently owing to their excellent light absorbing and emitting properties. Despite their excellent properties there are still problems that need to be overcome such as short operating lifetimes, and an observed hysteresis behavior in their current–voltage characteristics. It is found that these challenges could be overcome by developing a deterministic nucleation process using gold as a nucleation promoter to control the grain size of the perovskite layer. It is shown that this deterministic nucleation process can be expanded across multiple perovskite systems and can be used to achieve extremely uniform and large grain sizes within the perovskite layer. These large perovskite grains exhibit enhanced stability compared to current state‐of‐the‐art nanocrystalline films, and exhibit no hysteresis in their I – V characteristics which is key if commercialization of perovskites is to be realized. Abstract : A deterministic nucleation process is developed to achieve halide perovskite thin films with large and uniform grains using patterned Au arrays as nucleation promoters. The large and uniform grains restrict the ion migration processes in the halide perovskite thin films, leading to photodetectors with a low dark current and a high on/off ratio, and enhancing their stability in ambient environment.